Contracts scholarship beyond Materialisierung - Daniela Caruso (European Law Open, 2022)
This comment aims to show how Klaus Eller's paper on ‘The Political Economy of Tenancy Contract Law’1 raises the stakes of private law scholarship and contributes to the larger project of remodeling legal institutions in a progressive direction. The comment starts by contextualising the rapid spread of the Law and Political Economy (LPE) movement; illustrates through examples the generative impact of LPE on contemporary contracts scholarship; and highlights two strands of Eller’s original contribution to such literature: a welcome reflection on the value and limits of Materialisierung, and a radical widening of the private law inquiry to include institutional dimensions of legal reform. The point of fostering such new directions is not to ditch the very logic of private law and its endogenous mechanisms of justice, which are still essential to progressive legal work. What is no longer tenable is to keep seeking socially oriented solutions exclusively within the private law arsenal of possibilities, even when it has become obvious that only a synergic approach can produce accurate diagnoses of – and perhaps cures for – the structural predicaments of the market economy.